2016
DOI: 10.1007/s11920-016-0674-5
|View full text |Cite
|
Sign up to set email alerts
|

Electroconvulsive Therapy in the Elderly: New Findings in Geriatric Depression

Abstract: This paper reviews recent research on the use of electroconvulsive therapy (ECT) in elderly depressed patients. The PubMed database was searched for literature published within the past 4 years, using the search terms: "electroconvulsive elderly," "electroconvulsive geriatric," "ECT and elderly," and "ECT elderly cognition." The studies in this review indicate excellent efficacy for ECT in geriatric patients. Adverse cognitive effects of ECT in this population are usually transient and not typically severe. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 27 publications
1
28
0
1
Order By: Relevance
“…Still, despite the possible learning effects and the current debate on the reliability of the MMSE , this considerable increase is worth mentioning. In general, no negative evolution is seen in memory performance, which is in line with other studies . Contradictory to common beliefs, ECT has no long‐term deleterious effects on memory performance, on the contrary, memory performance seems to transcend pretreatment levels.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Still, despite the possible learning effects and the current debate on the reliability of the MMSE , this considerable increase is worth mentioning. In general, no negative evolution is seen in memory performance, which is in line with other studies . Contradictory to common beliefs, ECT has no long‐term deleterious effects on memory performance, on the contrary, memory performance seems to transcend pretreatment levels.…”
Section: Discussionsupporting
confidence: 89%
“…A profound consideration of this study is the limited generalizability due to the old‐age of our sample. However, since ECT is an effective treatment for elderly suffering from severe mood disorders , , , this study is of value for many patients treated with ECT. Furthermore, patients with the most pronounced cognitive deficits before the start of the treatment could not participate or dropped out in our sample, resulting in a ‘completer bias’.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A common risk factor for the majority of ECTinduced side effects is advanced age (van Schaik et al, 2015, Oudega et al, 2014. However, a recent metaanalysis demonstrated that advanced age is associated with more rapid ECT response rates and higher remission rates in rapid responders (Haq et al, 2015;Rhebergen et al, 2015;Geduldig and Kellner, 2016;Rosen et al, 2016). Thus, older individuals, who benefit most from ECT, may on the other hand have the highest risk for ECT-induced cognitive side effects.…”
Section: Introductionmentioning
confidence: 99%